STUNTING IN PREGNANCY OUTSIDE LEGAL MARRIAGE SOCIO-CULTURAL STUDIES IN RURAL TIMOR, KUATNANA DISTRICT, SOUTH CENTRAL TIMOR REGENCY, EAST NUSA TENGGARA, INDONESIA - Daniel Kameo; Petrus Christian Mboeik; Gatot Sasongko (Universitas Kristen Satya Wacana, 2025)
Background: The prevalence of stunting in Indonesia is still higher than the WHO maximum standard of 20 percent. East Nusa Tenggara is one of the Provinces in Indonesia that is still struggling with a high prevalence of stunting. The purpose of this study was to examine the incidence of stunting caused by socio-cultural factors related to pregnancy outside legal marriage in rural Timor, East Nusa Tenggara. Design and research method: A descriptive qualitative method along with a health anthropological approach were used to answer research questions. The cases being studied were the family of stunted toddlers under five years of age and their families with poor nutritional status. The initial survey was conducted on 108 stunted malnourished toddlers using a purposive sampling technique, 16 families with stunted children were selected for observation. Family activities were observed to learn about lifestyle, care of pregnant women, diet, and parenting patterns, as well as traditions carried out. In-depth interviews were conducted with the parents and grandparents of stunted children, the village head, village health workers, public figures, religious leaders, and traditional birth attendants in the study area. Results: Study results indicate that pregnancy outside of marriage occurs with couples without physical, mental, and financial readiness. It is also more common in people living in remote areas with traditional lifestyles who have low education and little knowledge and experience about health, pregnancy, and childcare. They are economically disadvantaged, including prospective fathers without a job and steady income. Conclusion and recommendation: Pregnancy outside legal marriage is one of the root causes that strongly influence social problems with an impact on the high incidence of stunting as well as malnutrition in rural Timor. To prevent and solve stunting problems, efforts are needed to overcome socio-cultural related stunting problems in rural Timor.